Stronger implicit interference in cognitively healthy older participants with higher risk of Alzheimer's disease. Issue 1 (20th September 2022) - Hung, Shao‐Min; Wu, Daw‐An; Shimojo, Shinsuke; Arakaki, Xianghong
Abstract: Introduction: Abnormal cerebrospinal fluid amyloid beta (Aβ)42 and tau levels have been revealed decades before symptoms onset in Alzheimer's disease (AD); however, the examination is usually invasive and inaccessible to most people. We thus aimed to develop a non‐invasive behavioral test that targets early potential cognitive changes to gauge cognitive decline. Specifically, we hypothesized that older cognitive healthy participants would exhibit comparable performance when the task was explicit and relied on conscious cognition. However, when the task was implicit, the performance of participants at high and low risks for AD would bifurcate. That is, early changes in unconscious cognition could be linked to cognitive health. Methods: We measured implicit interference elicited by an imperceptible distractor in cognitively healthy elderly participants with normal (low risk) and pathological (high risk) Aβ42 /total tau ratio. Participants were required to perform a Stroop task (word‐naming or color‐naming on an ink‐semantics inconsistent word) with a visually masked distractor presented prior to the target task. Results: We found that, under a high‐effort task (i.e., color‐naming in the Stroop task), high‐risk participants suffered interference when the imperceptible distractor and the subsequent target were incongruent in the responses they triggered. Their reaction times were slowed down by approximately 4%. This implicit interference was not found in the low‐risk participants. Discussion: These findings indicate that weakened inhibition of distracting implicit information can be a potential behavioral biomarker of early identification of AD pathology. Our study thus offers a new experimental paradigm to reveal early pathological aging by assessing how individuals respond to subperceptual threshold visual stimuli.